2021
DOI: 10.1111/os.13131
|View full text |Cite
|
Sign up to set email alerts
|

Microfracture of Acetabular Rim After Segmental Labral Resection to Restore the Morphology and Function of Labrum: A Retrospective Study of More than 2 Years Follow‐up

Abstract: Objective: To report on the clinical outcome of patients undergoing combined arthroscopic treatment of labral resection and microfracture at the rim of acetabulum at a minimum 2-year follow-up. Methods:The retrospective study included 38 patients undergoing hip arthroscopy for irreparable labral injury from 24 February 2014 to 26 February 2018. Thirteen patients were excluded owing to patient refusal of participation and concomitant diseases like synovial chondromatosis and dysplasia hip. The study group consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…(3) symptoms and imaging findings that were localized in the patellofemoral joint; (4) patients who suffered from malignant neoplasms; (5) patients who had active infection in other parts of the body; (6) female patients who were pregnant, lactating, or preparing for pregnancy; (7) cartilage lesions caused by infectious or gouty arthritis; (8) patients who had autoimmune diseases such as rheumatoid arthritis and ankylosing spondylitis; (9) patients who had diabetes with FBG over 8 mmol/L and had poor control; (10) patients who were generally in poor condition and unable to tolerate surgery; (11) patients who had severe diseases such as cerebral hemorrhage, severe pneumonia, and multiple organ dysfunction; (12) patients with Charcot joint; (13) any conditions that might increase the patient's risk or influence the results of the experiment during the research; (14) other reasons making the patient unsuitable for this study.…”
Section: Trial Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…(3) symptoms and imaging findings that were localized in the patellofemoral joint; (4) patients who suffered from malignant neoplasms; (5) patients who had active infection in other parts of the body; (6) female patients who were pregnant, lactating, or preparing for pregnancy; (7) cartilage lesions caused by infectious or gouty arthritis; (8) patients who had autoimmune diseases such as rheumatoid arthritis and ankylosing spondylitis; (9) patients who had diabetes with FBG over 8 mmol/L and had poor control; (10) patients who were generally in poor condition and unable to tolerate surgery; (11) patients who had severe diseases such as cerebral hemorrhage, severe pneumonia, and multiple organ dysfunction; (12) patients with Charcot joint; (13) any conditions that might increase the patient's risk or influence the results of the experiment during the research; (14) other reasons making the patient unsuitable for this study.…”
Section: Trial Participantsmentioning
confidence: 99%
“…Articular cartilage lesions of the knee are extremely common, with a high morbidity rate of 5% in the general population, and are characterized by the progressive loss of joint function and development of pain 1–6 . Currently, traditional conservative treatments for knee cartilage lesions include nonsteroidal anti‐inflammatory drugs, glucosamine, hyaluronic acid, and glucocorticoids 7–11 . However, as these therapies have limited therapeutic efficacy in the healing of cartilage lesions, their long‐term efficacy is uncertain 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our preliminary clinical outcome of microfracture at the acetabular rim is promising, and radiographic results have shown that the morphology and function of the labrum could be restored to a certain extent. 26 Despite that, there is no biological evidence regarding the potential advantages of bone marrow stimulation for the treatment of complete, irreparable labral tear. The histologic property of the regrown tissue and whether its volume is sufficient to fill the labral defect area remain unknown.…”
mentioning
confidence: 99%
“…In addition, our preliminary clinical outcome of microfracture at the acetabular rim is promising, and radiographic results have shown that the morphology and function of the labrum could be restored to a certain extent. 26…”
mentioning
confidence: 99%